2022
DOI: 10.1021/acsanm.2c02700
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Vanadate Micro/Nanostructures for Lithium-Ion Batteries

Abstract: The ability to control the composition and structure of inorganic compounds by simple synthesis methods is essential to the design and development of electrode materials of lithium-ion batteries (LIBs). Here we report the controllable synthesis of calcium vanadate micro/nanostructures via a simple hydrothermal method. By easily adjusting the pH value of a reaction system, a Ca10V6O25 straw-bundle-like structure, Ca2V2O7 microplatelet, and CaV6O16·3H2O sponge-like macrostructure can be selectively synthesized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The peak intensities of Zn 2p were significantly reduced after full charge (1.6 V), revealing the de-insertion of Zn 2+ . The high-resolution core-level Ca 2p spectrum is shown in Figure S4c of the Supporting Information, and the peaks appeared at 345 eV (2p 3/2 ) and 350.7­(2p 1/2 ) eV in their pristine state, which indicates the presence of Ca 2+ . No Ca 2p signals were observed in the charge and discharge states.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peak intensities of Zn 2p were significantly reduced after full charge (1.6 V), revealing the de-insertion of Zn 2+ . The high-resolution core-level Ca 2p spectrum is shown in Figure S4c of the Supporting Information, and the peaks appeared at 345 eV (2p 3/2 ) and 350.7­(2p 1/2 ) eV in their pristine state, which indicates the presence of Ca 2+ . No Ca 2p signals were observed in the charge and discharge states.…”
Section: Resultsmentioning
confidence: 99%
“…The high-resolution core-level Ca 2p spectrum is shown in Figure S4c of the Supporting Information, and the peaks appeared at 345 eV (2p 3/2 ) and 350.7(2p 1/2 ) eV in their pristine state, which indicates the presence of Ca 2+ . 78 No Ca 2p signals were observed in the charge and discharge states. This means that Ca ions do not participate in the electrochemical reactions, but they can serve as pillars.…”
Section: Zn-ion Storage Mechanism In Thementioning
confidence: 93%
“…The response, selectivity, recovery status, and humidity levels of CuObased gas sensors to H 2 S reported in the literature are summarized (Table 1). [49][50][51][52][53][54][55][56][57][58][59] Note that, the selectivity to 0.1 ppm H 2 S in this work was compared with 0.5-5 ppm of ethanol, acetone, hydrogen, or CO, respectively. Considering H 2 S high selectivity and recovery kinetics, 4Fe-CuO sensor exhibited prominent performance to quantify the H 2 S concentration in a high-humidity atmosphere (RH = 80%).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, designing micro-nano hierarchical structure materials can preserve the characteristics of nanostructures and combine the advantages of micrometer structures. [29][30][31][32] Besides, the crystal facets of the LNMO also affect its electrochemical performance. Previous studies have shown that choosing crystal facets with lower surface energy can help stabilize the crystal structure and reduce the occurrence of interfacial side reactions.…”
Section: Introductionmentioning
confidence: 99%